Chemistry informer libraries: a chemoinformatics enabled approach to evaluate and advance synthetic methods. Issue 4 (28th January 2016) - Kutchukian, Peter S.; Dropinski, James F.; Dykstra, Kevin D.; Li, Bing; DiRocco, Daniel A.; Streckfuss, Eric C.; Campeau, Louis-Charles; Cernak, Tim; Vachal, Petr; Davies, Ian W.; Krska, Shane W.; Dreher, Spencer D.
Abstract : We report a standardized complex molecule diagnostic approach using collections of relevant drug-like molecules which we call chemistry informer libraries. Abstract : Major new advances in synthetic chemistry methods are typically reported using simple, non-standardized reaction substrates, and reaction failures are rarely documented. This makes the evaluation and choice of a synthetic method difficult. We report a standardized complex molecule diagnostic approach using collections of relevant drug-like molecules which we call chemistry informer libraries. With this approach, all chemistry results, successes and failures, can be documented to compare and evolve synthetic methods. To aid in the visualization of chemistry results in drug-like physicochemical space we have used an informatics methodology termed principal component analysis. We have validated this method using palladium- and copper-catalyzed reactions, including Suzuki–Miyaura, cyanation and Buchwald–Hartwig amination.